THE EFFECT OF MANAGERIAL CAPABILITIES OF PRINCIPAL TOWARD SCHOOL QUALITY IN VOCATIONAL HIGH SCHOOL - Hasan KUSWANA (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2020)
The figure of principal as top management in schools has an important role in optimizing the function of teachers in accordance with the background of their expertise, particularly to vocational high school, which becomes one of Indonesian’s government priorities. Thus, the aim of the study was to examine the influence of the principal's managerial ability on the quality of vocational high school. The study was conducted at three public vocational schools of Business Management group located in North Jakarta. The study employed a quantitative survey method with 102 teachers as a sample from the teacher population of 138 people. Prior to the research, trials were conducted on 30 teachers. The research reports that direct influence of the principal's managerial ability on the quality of vocational school of business management group is 16%. This figure indicates the direct influence of the Principal's managerial ability on the quality of vocational high Schools. It is concluded that the competency of principal has a major role to bring the success of school as an educational organization and the quality of teachers